En hellenistisk møntskat fra Bahrain - Mørkholm, Otto (Kuml, 1972)
A Hellenistic Coin Hoard from Bahrain At the close of the 1969/70 excavation campaign on Bahrain, a pot was found containing Hellenistic silver coins. The excavator, Miss Else Roesdahl M.A., has kindly put the photograph fig. 1, which shows the pot in situ, at my disposal, together with the following description of the find context: "The pot containing the coins was found on 28th February, 1970, at the Qala'at al-Bahrain city mound in a thick occupation layer of sector 520. Around it were stones, possibly placed there as a support. The mouth was covered by a little bowl. Textile remains were found at the top of the pot. The pot lay below floor level in a partially excavated house of the same period as the occupation layer. The room in question was built onto the north face of the then disused north city-wall and opened onto a street passing through an opening in the old city-wall. The floor layer of the room was not clearly defined, but along several walls there was a 15 cm high plastered elevation. The pot was found when this elevation was demolished. lts connection with the building is uncertain, however, as no break in either the floor layer or the plastered elevation could be ascertained. The pot, its covering bowl and the potsherds from the occupation layer are characteristic of the city mound "City V" or "Glazed Bowl" Period (1)." On account of the general uncertainty of Hellenistic chronology in the whole Persian Gulf area it was very important to examine the coins and attempt to determine as accurately as possible the date of deposition of the hoard. In May, 1972, I paid a brief visit to Bahrain and had the opportunity to study there the 292 coins contained in the hoard (2). About 80 coins still awaited cleaning, and the investigation could therefore not be final. However, examination yielded such important information on the composition and chronology of the find that it seems reasonable to publish its results at this early stage, pending final publication. The coins could be classified as follows. Series I A (fig. 2) Obverse: Heracles-head bearing a lion skin, facing right; circle of dots. Reverse: Zeus seated, facing left, on a throne without a back-rest, with drapery around the lower body and crossed legs with left leg advanced: he holds an eagle on his outstretched right hand, while the left hand rests on a long sceptre; on the right AΛEΞANΔPOY; on the left, Arabic inscription Sh m s (inscription fig. 3, 15). 1. Obverse die no. 1. 2-3 " " " 2. Series I B (fig. 2) The same description applies as to series I A, but on the reverse left is the Arabic letter shin (fig. 3, 16); on the right is AΛEΞANΔPOY or slightly barbarized forms of this (fig. 8, 1-14). 4-11 Obverse die no. 3. 12-18 " " " 4. 19-26 " " " 5. Reverse inscription- variant no. 1. 27-33 " " " 6. " " " " 1. 34-39 " " " 7. 40-49 " " " 8. " " " " 1 & 2 50-51 " " " 9. " " " " 9. 52-64 " " " 10. " " " " 6, 11, 12 & 14 65-77 " " " 11. " " " " 11. 78-91 " " " 12. " " " " 8 & 14. 92-101 " " " 13. " " " " 10. 102-110 " " " 14. " " " " 1, 4 & 5. 111-130 " " " 15. " " " " 7 & 11 131-132 " " " 16. " " " " 3. 133-148 " " " 17. " " " " 12 & 13 149-215 Uncleaned specimens of series I B " " " " These 215 coins are closely related and undoubtedly derive from a single mint. They imitate Alexander the Great's tetradrachms in every detail. The closest parallels are found in the coins struck by the eastern mints of Babylon and Susa from the death of Alexander (323 B.C.) down to the beginning of the 3rd century B.C., when the name of the great conqueror was still used by his successors on their coins. It is, however, not possible to point to a direct prototype from which our coins have been slavishly copied. Their style is surprisingly good and their origin outside the true Hellenistic area is most clearly revealed in the unfamiliarity with the Greek letter forms which is apparent in so many inscriptions. One of the coins, no. 85 in the list, bears traces of overstriking. On the reverse between the Alexander inscription and Zeus's sceptre are the Greek letters ..ΣIΔE.. , remains of the Greek regal title BAΣIΛEΩΣ. Judging by the position of the letters, the overstruck coin was of the ordinary Seleucid type with a seated Apollo on the reverse (fig. 4 A), a representation which was introduced by Antiochus I at the beginning of his reign, around 280-278 B.C. The weight of the cleaned specimens ranges from 16.43 to 16.75 gm, while uncleaned specimens weigh about 17 .0 gm. There is thus no doubt that the coins, with respect to weight too, conform to Alexander's standard, by which tetradrachms should weigh about 17.2 gm. The somewhat lower weight of the cleaned specimens can be explained by a slightly heavy-handed removal of corrosion products. Coins 1-3 bear on the reverse the Arabic inscription Sh m s, which should be read Shams, a variant of the Semitic sun-god Shamash, who played a prominent role among the Arabs (3). The single letter Sh on the other coins is presumably an abbreviation for the same deity. The Greek Zeus on the reverse has thus been interpreted by the Arabs as a picture of their own great god of the heavens, Shamash. Four coins of the same type as no. 4-215 have been published previously as part of a great hoard from Susa, deposited about the middle of the 2nd century B.C. (4). The publisher of this find has rightly pointed out that this type of coin is related to other oriental Alexander-imitations, namely the slightly barbarized coins which comprised the greater part of the coin hoard from Failaka (fig. 4 B). These coins, which also occur in Hellenistic coin hoards from Syria and Asia Minor, can be dated to the end of the 3rd century B.C. and must on account of their more advanced barbarization be later than the coins from Bahrain (5). In the publication of the Failaka coins I referred the barbarized Alexanderimitations, on the basis of our information on the general trade relations in the Persian Gulf in Hellenistic times, to the important trading town of Gerrha on the Arabian coast just opposite Bahrain (KUML 1960, p. 203-204). This hypothesis, which has been favourably received, finds now same support in the Bahrain find, nearly three-quarters of which must be assigned to the same mint. It is hard to imagine a more appropriate origin for this considerable series of coins than neighbouring Gerrha. The 145 coins of Series I B which could be subjected to close examination have been struck with a total of 15 different obverse dies. We have thus slightly less than 10 specimens per obverse die, and statistical probability suggests that also the 67 uncleaned specimens were struck with the same obverse dies (6). The quite identical style and uniform condition of the coins suggests that they were struck within a relatively short period of time, and the high concentration of obverse dies indicate that our record of these dies is complete. It has been calculated that an obverse die could be used for at least 10,000 tetradrachms on an average (7), so this minting must have had a very considerable extent, which again shows that it must have been carried out at an important trading centre. Series II (fig. 5) Obverse: Heracles-head bearing lion skin, facing left; circle of dots. Reverse: Zeus seated, facing left, on a throne, with drapery around the lower body and crossed legs with the left leg advanced; he holds on his outstretched right hand the forepart of a horse (rhyton?), whilst the left hand rests on a long sceptre; on the right is an Aramaic inscription; on the left is a palm-tree and an indistinct Aramaic letter. 216. Obverse die no. 1. Uncleaned. Obverse: Heracles-head as above, but facing right. Reverse: As above, but under the palm-tree the Aramaic letter shin. 217. Obverse die no. 2. As previous specimen, but under the palm-tree on the reverse the Aramaic letter aleph. 218-219. Obverse die no. 2. 220. " " " 3. 221-222. " " " 4. 223-224. " " " 5. 225-231. " " " 6. As previous group, but under the palm-tree on the reverse is an ox's head in front view and on the extreme right the Arabic letter aleph (fig. 3, 17). 232-233. Obverse die no. 7. As 232-233, but on the reverse there is no letter on the extreme right. 234-239. Obverse die no. 7. As preceding, but on the reverse there is no letter or symbol under the palm-tree. 240. Obverse die no. 7. As no. 234-239 or 240. 241-245. Obverse die no. 7. Uncleaned. As no. 240. 246. Obverse die no. 8. 247. " " " 9. 248. " " " 10. 249. " " " 11. 250-251. " " " 12. 252-254. " " " 13. 255-258. " " " 14. 259-263. " " " 15. 264-275. " " " 16. 276-290. " " " 17. 291. " " " 18. Uncleaned 292. " " " 19. " In comparison with Series I the coins in Series II are far more barbarized. On the obverse, Heracles' lion skin is highly stylized, the eye, ear and nose of the animal being transformed into geometrical ornaments. The most striking feature of the stylization is the transformation of the lion's open jaws into a horn-like figure, which puts one in mind of Ammon's ram's horn, which Alexander the Great in certain portrayals bears as a sign of his descent from that divinity. Heracles' ear and the hair on his forehead and in front of his ear is also reproduced in a stiff schematic fashion. The seated figure on the reverse of the coins is as awkward as a child's drawing. The head is in several instances disproportionately large, the limbs stiff and the musculature of the upper body reproduced schematically. An original innovation is the forepart of a horse in the god's right hand, replacing the original eagle. In certain specimens (no. 240 and no. 276) the body of the horse is bent, which puts one in mind of the so-called rhyta, Persian drinking-vessels of precious metal which terminate in various animal figures. In front of the god is a palm-tree (clearest in no. 255), which is often shown as a strangely twisted bundle of branches or twigs. Under this palm-tree there is in a number of coins an Aramaic letter (shin in no. 217; aleph in no. 218-231) or a symbol - an ox's head in front view (in no. 232-239). Analogous with other Hellenistic coin series, such letters and symbols may indicate the authorities responsible for each minting. Especially interesting is the Arabic aleph in no. 232-233, because it strengthens the connection between these coins and an exactly corresponding series of coins with purely Arabic inscriptions, a couple of examples of which have been found in Susa. The weighed specimens of these coins have a weight of 16.52-16.68 gm in the cleaned state. Uncleaned coins weigh about 17 .0 gm. Series II was thus like the first series minted in accordance with the Attic weight standard, which was introduced by Alexander the Great throughout his extensive empire. The Aramaic inscription is often very difficult to decipher and apparently contains a number of variant spellings (fig. 6). It is practical to begin an analysis with the two letters b r, which occupy the middle of the inscription and are nearly everywhere distinct. Since this word means 'son' in Aramaic, it shows that we are here confronted with an inscription of the common type "X, son of Y". We are thus justified in looking for a personal name both before and after b r. The name preceding b r is normally written with four letters (inscription no. 221, 232, 240), of which the first three are distinct - aleph, beth, aleph - whilst the fourth has been read as n or l. Since the latter reading is the most likely we obtain the transcription 'b'l or 'ab'al. This clear-cut result is complicated by the fact that at least one inscription (no. 225) clearly has five letters preceding b r. The extra letter is in third place and most closely resembles an l, which gives the transcription 'bl'l or 'abl'al. A similar variation is found in the paternal name following b r. The first letter in this name is a distinct t; then follows what appears to be an l (n has been suggested), while the third letter is usually a distinct sh (shin). However, a b is sometimes (no. 221 and 225) interposed in third place, followed by sh as fourth letter. With this shin the inscription in many cases closes, but sometimes (no. 232 and 240) it continues with a further two or three letters, which as a rule are very difficult to decipher and vary widely in appearance in the few distinct specimens. It is thus a task for a Semitic epigraphist to carry out the final reading of the inscription (8). As a result of this discussion I suggest the following transcription, with more sporadically occurring letters in brackets: 'a b(l)'a l br tl(b)sh ... In Series II, comprising 77 coins, 19 different obverse dies have been registered. There are thus only 4 coins per obverse die and we may therefore assume that other obverse dies will appear, so that the issue can have had a greater volume than the coin hoard itself would indicate directly (see note 6 above). Chronology As mentioned above, one specimen of Series I B (no. 85) has been struck on a Seleucid coin which cannot antedate the first year of the reign of Antiochus I, 280 B.C. This year may thus be regarded as the earliest limit or terminus post quem for the production of Series I B. A corresponding latest possible limit (terminus ante quem) is obtained by dating the barbarized Failaka coins, which besides the Failaka find from about 205 B.C. occur in two finds from Gordion in Asia Minor, which must be dated to about 200 B.C., and in an as yet unpublished find from Syria which was apparently deposited about 190 B.C. (see note 5). On the assumption that Series I B is an earlier issue from the same mint as the more primitive Failaka coins, we obtain a terminus ante quem for Series I B of around 210 B.C. Within the period of time thus established, 280 to 210 B.C., it is difficult to arrive at an exact dating. The stylistic gap between our Series I B and the Failaka type is very large, but it is not possible to employ this stylistic decline to give a more exact chronological placing within the brackets already given. A mintage date for Series I A of about 240 B.C. and for Series I B og about 240-230 B.C. seems to me to be both reasonable and likely. The coins of Series II with Aramaic inscription make no independent contribution to the chronological evaluation. Two specimens have been found in Susa with coins of Series I B, but since the hoard in question was deposited in the latter half of the 2nd century B.C., it has only little significance for the dating of the coins of our type, which belong to its older components (9). Judging by the state of preservation of the coins in the Bahrain find they must be roughly contemporaneous with Series I B. Since the majority of the coins of both these series are extremely well preserved, the hoard must have been deposited shortly after minting. The probable date of deposition must therefore lie around 230 B.C., with a margin of error of 15 years to both sides. We can be reasonably sure that the hoard was deposited between 245 and 215 B.C. Attribution While Series I A and I B may with some probability be referred to Gerrha, Series II presents us with a new attribution problem. A couple of coins of exactly the same type and style, but with Arabic inscription, were present in the above-mentioned Susa find from the middle of the 2nd century B.C. (10). On these coins the inscription h r th t m l k h g r or 'Harithat, King of Hagar' (fig. 7) is distinct. The tendency has been to place Hagar in northern Arabia, where a tribe which the Greek sources call the Agraioi controlled the most easterly stretch of the caravan road from Babylon via Dumaitha (Djof) and Petra to the Mediterranean coast at Gaza or to the Egyptian delta (11). There is, however, another possibility. According to some medieval Arab geographers, the large oasis area around Hufhuf had at that time the name al-Hagar. This may possibly be the tribe mentioned by Pliny, who speaks of gentes Agraei (12). These Agraei, who cannot be identified with Strabo's Agraioi, have hitherto usually been placed in southern Arabia, but the most recent study has entertained the possibility that the description in Pliny refers to a caravan route from south Arabia to be east coast of the peninsula terminating in Hufhuf, and that gentes Agraei should be placed there (13). Whatever the truth contained in these unclear texts, it is much easier to imagine the coins from Hagar and thus also our Series II with Aramaic inscription, which in type and style are absolutely identical, as having been minted on the Arabian mainland in the vicinity of Bahrain than far to the north between Babylon and Petra. Furthermore a solitary coin belonging to Series II has been found as a loose find in the Thaj oasis, about 170 km north of Hufhuf (14). On the map fig. 8 a number of localities which have been identified with ancient Gerrha are indicated with +. Placing gentes Agraei in Hufhuf removes the possibility of placing Gerrha there. Furthermore, it transpires clearly from our most reliable geographical sources, Strabo and Pliny, that Gerrha should be sought in the region north of Bahrain, since that locality under the name Tyros or Tylos is mentioned after Gerrha in their description of the east Arabian coast, moving from north to south (15). If Gerrha was situated on the coast, Qatif becomes the most likely locality suggested so far, but a situation somewhat further north on the east coast is still a possibility, whereas localities like Uquair, Salwa and Duwayhin can be left out of consideration. However Strabo, who bases his description of these regions on the 3rd century B.C. work of the great geographer Eratosthenes, states that the actual city of Gerrha lay 200 stades, or not quite 40 km, inland from the coast. To my knowledge no localities with ancient remains at exactly that distance from the coast have been pointed out. At about 7 5 km from the coast, at the Thaj oasis, quite extensive remains have been found and numerous surface finds from the locality show that there was a town there in Hellenistic times. Since the ancient distances have so often been distorted in the sources, and since the coastline may have changed position, it is possible to place Gerrha in the Thaj oasis, but the final solution of this problem must await regular archaeological excavations in the area in question (16). Whatever Gerrha's exact situation on or near the east coast of Arabia, the coin hoard from Bahrain is of great historical importance in itself. We now know of two Hellenistic coin series from the region, both of Attic weight and both from the latter half of the 3rd century B.C. The occurrence of locally minted coins testifies to the extension of Hellenistic culture to this marginal area. The employment of the Attic standard shows that trade from east Arabia in this period was mainly oriented towards the Seleucid empire, where the same weight standard obtained, and the finds of these east Arabian Alexander-imitations on Failaka, in Susa, northern Syria, and Gordion in central Asia Minor show the routes by which trade was conducted. The numismatic material thus supplements other historical information on Arab trade in the Hellenistic period and corrects to a certain extent the impression that Ptolemaic Egypt with its special coin standard and mercantile economy was able to entirely dominate trade with oriental luxury articles in this period. Otto Mørkholm